Enhancing Educational Excellence: Elevating Learning Quality Through Podcast-Based Arts Performances in Pesantren - Umar Manshur; Nurul Makiyah (Journal of Islamic Education Research, 2024)
This research uses a qualitative case study approach to analyze the use of podcast-based arts performances in improving the quality of Arabic language learning for students. Data collection was carried out through interviews, observation and documentation. Data analysis involves collecting, reducing, presenting, and drawing conclusions. The research results show the effectiveness of podcast arts performances in improving students' Arabic language skills and creating a creative learning atmosphere. Implementation involves planning, implementing, and evaluating the program. The research implications suggest that podcast-based arts performances can effectively improve Arabic language skills among Islamic boarding school students. Recommendations are given to educational institutions to consider integrating podcast-based arts performances to increase the effectiveness of Arabic language learning.